The Influence of the Interaction Environment of Islamic Education Students at IAIN Kerinci on Their Religious Character - Nagiya Nagiya; Pristian Hadi Putra; Albertos Famni (Yayasan Rahmat Islamiyah, 2026)
This study aims to examine the influence of student interactions on religious character. The social environment plays a crucial role in shaping an individual's character therefore, this research explores the extent to which social interactions impact the development of religious values. The study employs a quantitative method using a cluster random sampling approach, where data were collected through questionnaires and analyzed using Descriptive Statistical Mean. The findings indicate that peer interactions have a significant influence on religious character, with an average relationship score of 65. These results highlight the importance of the social environment in shaping religious character and provide insights for educational institutions to better manage and facilitate social interactions to effectively support the development of students' religious values.